THE LEGISLATION AND EDUCATIONAL POLICIES IN BRAZIL IN THE PREVENTION OF DIGITAL STALKING CASES RELATED TO YOUNG PEOPLE AND ADOLESCENTS. (CIPEEX, 2026)
This article analyzes the effectiveness of Law No. 14.132/2021 in combating digital stalking in Brazil, especially among young people and adolescents. The research employs the comparative law method to analyze the legislation and cyber education policies of Brazil and Portugal. Bibliographic and documentary analyses were conducted using databases such as Scielo, Google Scholar, and national and international legislation. The hypothesis is that legislation, combined with educational policies, is essential for the effective prevention of digital stalking. The study was developed by Aline Vitória Machado (student) and Leidiane de Morais e Silva Mariano (professor).